2022
DOI: 10.3390/jcm11020333
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia Nociception Index-Guided Remifentanil versus Standard Care during Propofol Anesthesia: A Randomized Controlled Trial

Abstract: The clinical benefits to be expected from intraoperative nociception monitors are currently under investigation. Among these devices, the Analgesia Nociception-Index (ANI) has shown promising results under sevoflurane anesthesia. Our study investigated ANI-guided remifentanil administration under propofol anesthesia. We hypothesized that ANI guidance would result in reduced remifentanil consumption compared with standard management. This prospective, randomized, controlled, single-blinded, bi-centric study inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
0
23
0
1
Order By: Relevance
“…The ANI interval recommended by the manufacturer for 'adequate analgesia' is 50-70. In adults, ANI guidance of intraoperative opioids has resulted in an intraoperative opioid-sparing effect [31,32], lower pain scores and reduced fentanyl consumption in the postanesthesia care unit [33].…”
Section: Analgesia Nociception Indexmentioning
confidence: 99%
“…The ANI interval recommended by the manufacturer for 'adequate analgesia' is 50-70. In adults, ANI guidance of intraoperative opioids has resulted in an intraoperative opioid-sparing effect [31,32], lower pain scores and reduced fentanyl consumption in the postanesthesia care unit [33].…”
Section: Analgesia Nociception Indexmentioning
confidence: 99%
“…Several studies have adjusted the dose of remifentanil or fentanyl to maintain the ANI around 50–70 during general anesthesia, and they revealed that ANI-guided management can reduce intraoperative opioid consumption without deteriorating postoperative outcomes [ 36 40 ]. Sabourdin et al investigated ANI-guidance versus standard care in elective gynecologic surgery ( n = 80) under target-controlled infusion of propofol and remifentanil [ 37 ]. They showed that intraoperative remifentanil consumption was lower in the ANI-guided group [4.4 vs 5.8 µg/kg/h, difference of −1.4; 95% confidence interval (95% CI) −2.6 to −0.2, p = 0.0026] with no difference in postoperative morphine consumption.…”
Section: Does Ani Contribute To Opioid-sparing Anesthesia?mentioning
confidence: 99%
“…Regarding the potential of ANI, Anderson et al described that ANI-based analgesia has the potential to be good for individualized titration of anesthesia management [ 63 ], and trials of ANI-based goal-directed analgesia are currently underway [ 64 ]. If ANI/HFVI studies are accumulated and their validity is confirmed, ANI-based administration may be realized [ 37 ]. A machine learning-based method combining ANI and hemodynamic monitoring has already been investigated with continuous administration of remifentanil [ 65 ].…”
Section: Outlooks Of Ani/hfvimentioning
confidence: 99%
“…The analgesia nociception index (ANI) is an index that measures the high-frequency component of heart-rate variability (parasympathetic component of the autonomic response) using the electrocardiogram signal as an input on a scale from 0 (maximum of nociception) to 100 (complete analgesia) [23][24][25][26]. Based on the published studies [23][24][25][26], an ANI of between 50 and 70 may correspond to adequate antinociception. Gruenewald et al reported that ANI enabled consistent reflection of stimulation during propofol-remifentanil anesthesia [23].…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer patients under GA, use of ANI monitoring can help optimize opioid consumption and provide data about nociception/antinociception intraoperatively [25]. Recently, in a randomized controlled trial, Sabourdin et al demonstrated that ANI guidance resulted in lower remifentanil consumption compared with standard practice under propofol and remifentanil anesthesia [26]. In previous clinical studies of RP mixtures, their monitors only included the hemodynamic monitors and sometimes a bispectral index (BIS) monitor, and there was no ANI monitor.…”
Section: Introductionmentioning
confidence: 99%